Effects of an energy drink on myonectin in the liver, kidney and skeletal muscle of exercised rats - Avcu, Emsal Cagla; Cinar, Vedat; Yasul, Yavuz; Akbulut, Taner; Pancar, Zarife; Aydemir, Isa; Aydin, Suleyman (Taylor & Francis Ltd, 2024)
Myonectin is a hormone that is produced mainly by skeletal muscle. We investigated the effects of exercise and energy drink (ED) administration on myonectin expression in skeletal muscle, liver and kidney tissue in rats; myonectin is produced by all three tissues. We used 28 male albino rats in four groups: untreated control (C), exercise (E), energy drink (ED) and exercise + energy drink (E + ED). The E and E + ED groups were exercised using a treadmill for 4 weeks. We also administered 3.5 ml/kg/day ED during week 1, 7 ml/kg/day during week 2 and 10 ml/kg/day during weeks 3 and 4 in the E and E + ED groups. We used ELISA to measure the levels of myonectin in skeletal muscle, liver and kidney tissues. We used immunohistochemical staining to investigate the localization and intensity of myonectin in these tissues. The amount of myonectin in skeletal muscle tissue was increased significantly in all experimental groups compared to group C. The amount of myonectin in the ED group was significantly greater than group E. No significant difference was observed in liver tissue; however, the amount of myonectin in the liver of group C was the greatest among all groups. The amount of myonectin in kidney tissue exhibited no significant difference among groups. Consumption of ED during exercise increased the amount of myonectin in kidney and skeletal muscle tissues and decreased it in liver tissue. We suggest that consumption of ED might adapt metabolism to incresed exercise by controling synthesis of myonectin in liver, kidney and skeletal muscle.
Keywords: Energy drink; exercise; kidney; liver; myonectin; rats; skeletal muscle